ANALYSIS OF PUSKESMAS MANAGEMENT IN RELATION TO SERVICE OPTIMIZATION AT BENGKOL MANADO PUSKESMAS - Sheila Clarisa Korayan; Hery Winoto Tj; Fushen (RADJA PUBLIKA, 2023)
The purpose of this study is to analyze the management of Puskesmas (Community Health Center) in relation to optimal service delivery at Bengkol Puskesmas. The data used is of qualitative method, employing a phenomenological approach, located at Bengkol Puskesmas in Manado. The information sources were derived from three informants. The data is supported by secondary data from reference books related to the research. The analysis method employed in this study involves several stages of data analysis techniques, beginning with data collection through in-depth interviews, observations, and documentation. The findings of this research indicate that there is an excessive or dual workload at Bengkol Puskesmas in Manado and a lack of human resources with expertise in fields such as science, technology, and nutrition. There are plans for optimizing health service management and ensuring good health facilities, allowing for optimal community health services. Despite some health program activities experiencing delays beyond the planned schedule due to a shortage of human resources, effective health services for the community can still be achieved.